Spiritual Profile of Muslim Entrepreneurs in MSMEs: A Study of Islamic Boarding School-Based Entrepreneurship - Tuti Nadhifah; Dian Rosita; Heni Risnawati; Alisah Yudiana; Lilien Ristina (www.amertainstitute.com, 2025)
This ponder points to look at the most profound sense of being profile of Muslim business people within the Miniaturized scale, Little, and Medium Endeavors (MSME) segment based in Islamic boarding schools (pesantren). The investigate is persuaded by the noteworthiness of otherworldly values in entrepreneurial hones, especially within the setting of pesantren, which coordinating Islamic values with financial exercises. This subjective inquire about employments a case consider approach including a few pesantren-based business visionaries within the Java locale. Information were collected through in-depth interviews, participatory perception, and documentation. The discoveries uncover that Muslim entrepreneurs' otherworldly existence is reflected in astuteness, trustworthiness, persistence, believe in God (tawakkul), and commitment to sharia standards in commerce operations. This otherworldly existence serves as a ethical and ethical establishment in confronting trade challenges and shapes a administration fashion that's sympathetic and mindful. The consider highlights the key part of pesantren in sustaining Muslim business people who are not as it were financially competent but moreover profoundly grounded.